Learning Disabilities in Malnourished children - Sandhya Chandran (Department of Home Science, College of Agriculture, 2001)
The study entitled "Learning Disabilities in Malnourished Children" undertaken in the rural areas of Trivandrum district was conducted to study the relative effect of malnutrition on the learning disabilities of children between